Mutual Cooperation in the Formal Allyl Alcohol Nucleophilic Substitution and Hydration of Alkynes for the Construction of γ‐Substituted Ketones. Issue 19 (22nd March 2016) - Huang, Kaimeng; Wang, Hongkai; Liu, Lingyan; Chang, Weixing; Li, Jing
Abstract: Mutual cooperation in the formal allyl alcohol nucleophilic substitution reaction and hydration of an alkyne has been utilized in the presence of a gold catalyst to give a series of γ‐functionalized ketones with high to excellent yields. This reaction actually involved an intramolecular O−H insertion cyclization of an alkyne to form the dihydrofuran intermediate, which was followed by the nucleophilic addition ring‐opening of a dihydrofuran to give the target compound. Abstract : Cooperation is key ! Mutual cooperation in the formal allyl alcohol nucleophilic substitution reaction and hydration of an alkyne has been utilized in the presence of a gold catalyst to give a series of γ‐functionalized ketones with high to excellent yields (see scheme).